Nurr1 deficiency impairs autophagy-lysosomal function through GBA-dependent transcriptional regulation in Parkinson’s disease pathogenesis - Cheng, Cheng; Yang, Huijia; Tian, Lulu; Ni, Yang; Jia, Congcong; Le, Weidong; Wang, Qingshan (Frontiers in Aging Neuroscience, 2025)
IntroductionThe autophagy-lysosomal pathway (ALP) dysfunction and lysosomal impairment contribute to the pathogenesis of Parkinson’s disease (PD). Nuclear receptor related protein 1 (Nurr1) maintains the differentiation and maturation of dopaminergic neurons, and mutants or polymorphism in Nurr1 is associated with familial and sporadic PD. Previous studies on Nurr1 have mainly focused on the development and maintenance of midbrain dopaminergic neurons, while the potential involvement of Nurr1 in ALP regulation remains uncharacterized.MethodsStable Nurr1 knockdown cells and inducible Nurr1 knockout mice were generated. Transcriptome sequencing and analysis was utilized to confirm the altered pathways and differentially expression genes associated with ALP. Transmission electron microscopy observation was conducted to find the ultrastructure differences between the Nurr1 knockdown cells and the controls. The expression of LC3B and the colocalization of LC3B and Lamp1 were assessed. Lysosomal acidity in the Nurr1 knockdown cells and the controls was measured. The expression of lysosomal proteins (Lamp 1/2, CTSD, and GBA) was determined in vitro and in vivo in the Nurr1-deficient models. Dual-luciferase reporter gene assay was performed to detect the transcriptional activity of GBA. The key lysosomal proteins (Lamp 1/2 and CTSD) were assessed after GBA overexpression.ResultsTwenty-two terms and 45 differentially expression genes associated with ALP were identified by transcriptome analysis. Knockdown of Nurr1 induced intracellular aggregation of autophagosomes, increased endogenous expression of LC3B II and elevated colocalization of exogenous GFP-LC3B with Lamp1. Lysosome dysfunction has been implicated with lysosomal alkalization and deprived level of lysosomal marker proteins with Nurr1 deficiency. GBA was transcriptionally downregulated by Nurr1 and Nurr1 deficiency-triggered lysosomal dysfunction were attenuated by GBA overexpression in the Nurr1 knockdown cells.DiscussionOur study provided the first experimental evidence that Nurr1 deficiency induced lysosomal dysfunction by alkalizing the lumen of lysosomes and downregulating the key lysosomal protein (Lamp1, CTSD, and Lamp2) expression in vivo and in vitro. Defective lysosomal function compromised lysosomal mediated autophagic vesicle clearance. Mechanistically, Nurr1 transcriptionally regulated GBA expression, which in turn governed lysosomal marker protein homeostasis through a GBA-dependent axis. This study illuminated the involvement of Nurr1 in the ALP and the interaction between PD-related genes in the pathogenesis of PD.